Motivating school pupils in rural areas for enhanced English proficiency - Mohamed Ali, Haja Mohideen (2015)
Many studies have emphasized the role of motivation in second language learning. It plays a key role in the acquisition of knowledge, skills and language proficiency besides others. In most disciplines of learning, we have to be sufficiently motivated to pursue our goals and achieve the objectives. It is obvious those who are motivated may be expected to perform better. Not all learners may be motivated enough to reach the targets set. The teacher can help to motivate the learners through various means. Lack of motivation is a serious problem. According to a 2003 report on motivation in schools in USA, upwards of 40% of secondary school students have become chronically disengaged from school (Crotty, 2003). By comparison, students who are motivated to learn record higher achievement scores. Such students are more satisfied with school and better understand the concepts they are exposed to.